Utilization potential of agro-industrial by-products and waste sources: Laccase production in bioreactor with Pichia pastoris - Caloglu, Buse; Binay, Baris (Elsevier, 2023)
Valorization of waste materials has been an attractive approach due to ensuring circular bioeconomy model in bioprocesses depending on annual billion metric tons production of agro-industrial by-products and wastes. With being an influential platform of Pichia pastoris fermentation to produce value-added bioproducts, especially for recombinant proteins, the studies have been gaining speed to apply the circular bioeconomy model to these processes by enhancing production efficiency. In this study, solid and liquid dextrose from a local corn processing industry and watermelon peel from a local market were evaluated for production of Madurella mycetomatis laccase from P. pastoris X33 in a bioreactor. When compared to fermentation including alternative sources and glycerol/methanol which was performed as a control study, almost 2-fold higher laccase activity with 41 g DCW/ L and 1.30-fold increase in laccase activity with 50 g DCW/L were determined, respectively for fermentation strategies including solid dextrose and liquid dextrose. Maximum laccase activity was obtained from watermelon peel hydrolysate utilization although lowest cell density was obtained in the growth stage. One-way ANOVA analysis confirmed the effect of carbon sources encouraging heterologous protein production in P. pastoris expression system. These results proved suitability of bioprocesses which were designed for the valorization of solid/liquid dextrose and watermelon peel hydrolysate as alternative carbon sources in P. pastoris fermentation for future scale-up.
Keywords: Agro-industrial wastes; Pichia pastoris; Laccase enzyme; Bioprocess development; Circular bioeconomy